Sosialisasi Pengelolaan Jurnal Berbasis OJS (Persiapan Jurnal Society Untuk Mahasiswa Sosiologi Fisip UTU) - Triyanto Triyanto; Rahmah Husna Yana; Irma Juraida; Nurkhalis Nurkhalis; Desi Maulida; Nodi Marefanda; Akmal Saputra (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
AbstractMany OJS-based journal managers do not understand the steps that should be taken. Many still publish by relying on back issues, even though the applications used are already based on OJS. The important thing that becomes the question is how is the real management of OJS-based scientific journals? For this reason, it is very important to carry out this socialization to increase the capacity of journal managers so that they can be even better and by the applicable standards in OJS. The method of implementation is face-to-face with the presentation of material in the form of material slides. Participants who attended were journaled managers who had frequently opened the OJS application so that in general they understood how the OJS application worked. However, this participant needs to be deepened considering that several steps are often missed in journal management. The results of the socialization showed that the participants had increased their understanding of step by step journal management. This can be seen from the results of discussions or questions and answers at the end of the material presentation session. Thus it can be concluded that the journal society is ready to be operationalized or ready to accept article manuscripts from students.